Estimating the Neutralizing Effect and Titer Correlation of Semi-Quantitative Anti-SARS-CoV-2 Antibody Immunoassays - Lee, Beomki; Ko, Jae-Hoon; Park, Jiho; Moon, Hee-Won; Baek, Jin Yang; Jung, Sunhee; Lim, Hee-Young; Kim, Kyung-Chang; Huh, Kyungmin; Cho, Sun Young; Kang, Cheol-In; Chung, Doo Ryeon; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
For the clinical application of semi-quantitative anti-SARS-CoV-2 antibody tests, the analytical performance and titer correlation of the plaque reduction neutralization test (PRNT) need to be investigated. We evaluated the analytical performance and PRNT titer-correlation of one surrogate virus neutralization test (sVNT) kit and three chemiluminescent assays. We measured the total antibodies for the receptor-binding domain (RBD) of the spike protein, total antibodies for the nucleocapsid protein (NP), and IgG antibodies for the RBD. All three chemiluminescent assays showed high analytical performance for the detection of SARS-CoV-2 infection, with a sensitivity ≥ 98% and specificity ≥ 99%; those of the sVNT were slightly lower. The representativeness of the neutralizing activity of PRNT ND50 ≥ 20 was comparable among the four immunoassays (Cohen’s kappa ≈ 0.80). Quantitative titer correlation for high PRNT titers of ND50 ≥ 50, 200, and 1,000 was investigated with new cut-off values; the anti-RBD IgG antibody kit showed the best performance. It also showed the best linear correlation with PRNT titer in both the acute and convalescent phases (Pearson’s R 0.81 and 0.72, respectively). Due to the slowly waning titer of anti-NP antibodies, the correlation with PRNT titer at the convalescent phase was poor. In conclusion, semi-quantitative immunoassay kits targeting the RBD showed neutralizing activity that was correlated by titer; measurement of anti-NP antibodies would be useful for determining past infections.